Bone Piezosurgery in Oral and Maxillofacial Region - G. Pavlíková; R. Foltán; E. Horká; T. Hanzelka; J. Šedý (Czech Dental Chamber, 2010)
The review summarizes present knowledge and experience with bone piezosurgery, which represents a perspective soft tissue-friendly technique of bone surgery, which is based on ultrasound microvibrations. The main advantage of piezosurgery include protection of soft tissues, a high degree of orientation in the operation field, decreased blood loss, less vibrations and noise and a higher comfort to the patient. Piezosurgery has been so far used in various indications: otolaryngology, oral and jaw surgery, neurosurgery, ophthalmology, traumatic medicine or orthopedics. The main indications of piezosurgery in the area of oral surgery include: sinus lift, preparation of the implant bed, extension of alveolar process, sampling of bone grafts, osteogenic distraction, supportive osteotomy in orthognathic surgery, retrograde endodontic surgery, periodontium surgery, removal of cysts, tooth extraction, deliberation of alveolar inferior nerve and other interventions in the neighbourhood of anatomical structures at risk. Piezosurgery represents a perspective technology in various area of bone surgery.